2016
DOI: 10.1111/padm.12237
|View full text |Cite
|
Sign up to set email alerts
|

Managing Social Capital and Diversity for Performance in Public Organizations

Abstract: Managers concerned with the performance of their organizations will exploit available social, administrative, and human capital resources. However, extant theory and mixed empirical evidence leave the effect of social capital on performance unclear. The gains from these norms of reciprocity, participation, networking, and trust may disproportionately benefit only some of their clients, leading to disparities in outcomes among diverse clienteles. We argue that in such contexts, management will put in place poli… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
20
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 22 publications
(22 citation statements)
references
References 58 publications
2
20
0
Order By: Relevance
“…This article makes an original contribution by exploring the opportunities and challenges of employing soft metagovernance to promote public value in governance networks. It provides new insights into how public value is (de)constructed as a consequence of soft metagovernance in multi‐agency settings as leaders seek to exploit ‘social capital resources’ (Compton and Meijer ). A number of critical observations are made.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…This article makes an original contribution by exploring the opportunities and challenges of employing soft metagovernance to promote public value in governance networks. It provides new insights into how public value is (de)constructed as a consequence of soft metagovernance in multi‐agency settings as leaders seek to exploit ‘social capital resources’ (Compton and Meijer ). A number of critical observations are made.…”
Section: Discussionmentioning
confidence: 99%
“…Some of these tangible returns from employing soft metagovernance were shared at the staff focus group. Social bonds and capital were recognized as pivotal to making things happen formally (Compton and Meijer ) and creating public value. Nonetheless, Bristol£ staff suggested that soft metagovernance is most often used at an individual level and is largely ad hoc in its application.…”
Section: Research Findingsmentioning
confidence: 99%
“…In social science, social capital is widely viewed as an important cause of public spiritedness, political participation, government responsiveness and economic development (McDonough et al ; Seligson ; Gibson ; Knack ). The importance of social capital has received increasing attention from public administration scholars and practitioners in recent years, since social capital determines the nature and intensity of interactions between citizens in a community and powerfully influences the performance of public organizations (Brewer ; Andrews and Brewer ; Piatak ; Williamson and Bond ; Compton and Meier ).…”
Section: Theoretical Expectations and Hypothesesmentioning
confidence: 99%
“…Social capital as a concept has been used in a wide range of public administration research. This ranges from Compton and Meier's (2016) use of an index of survey items including trust, PTA involvement, and self-reported civic participation to demonstrate a relationship between social capital and diversity management practices in public schools, to the use of social network analysis to explore the management of effective forest planning (Paletto, Hamunen, and De Meo 2015). It is a powerful tool to foster economic development and overcome collective action problems.…”
Section: The Current State Of Social Capital and Economic Developmentmentioning
confidence: 99%